2021
DOI: 10.31577/sp.2021.02.820
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Personality Traits, Religiosity and Spirituality as Predictors of Epistemically Unfounded Beliefs

Abstract: The present research focuses on the question whether spirituality, religiosity and maladaptive personality traits, as measured by the PID-5 (antagonism, psychoticism, disinhibition, negative affectivity, detachment), predict epistemologically unfounded beliefs (conspiracies, pseudo-science and paranormal beliefs). The sample included 829 participants recruited through social networks (58% women, mean age 29.98 years). The results showed that especially psychoticism is a positive predictor of all types epistemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This undefinable power is a fundamental feature of conspiracy thinking ( Galliford and Furnham, 2017 ). Although in some studies religious individuals were more likely than non-religious ones to believe in conspiracy theories ( Kim and Kim, 2021 ; Leibovitz et al, 2021 ; Tonković et al, 2021 ; Freeman et al, 2022 ), other studies found no significant relationship (e.g., Agley and Xiao, 2021 ; Andrade, 2021c ; Furnham, 2021 ; Teličák and Halama, 2021 ), or the relationship was different for different CBs scales ( Atari et al, 2019 ). In a study by Jasinskaja-Lahti and Jetten (2019) , no differences were found between endorsement of CBs between believers and non-believers.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…This undefinable power is a fundamental feature of conspiracy thinking ( Galliford and Furnham, 2017 ). Although in some studies religious individuals were more likely than non-religious ones to believe in conspiracy theories ( Kim and Kim, 2021 ; Leibovitz et al, 2021 ; Tonković et al, 2021 ; Freeman et al, 2022 ), other studies found no significant relationship (e.g., Agley and Xiao, 2021 ; Andrade, 2021c ; Furnham, 2021 ; Teličák and Halama, 2021 ), or the relationship was different for different CBs scales ( Atari et al, 2019 ). In a study by Jasinskaja-Lahti and Jetten (2019) , no differences were found between endorsement of CBs between believers and non-believers.…”
Section: Resultsmentioning
confidence: 93%
“…These general constructs of conspiratorial functioning constitute universal predispositions, not determined by sociopolitical or cultural contexts. CBs were also investigated as a part of a wider category of “unfounded beliefs” ( Teličák and Halama, 2021 ). The generality of belief hypothesis (i.e., the generality of endorsement of various unsubstantiated claims, such as unsubstantiated conspiracy theories, scientific and psychological misconceptions, or paranormal beliefs) received support ( Bensley et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the empirical evidence for the relationship between religiosity, spirituality, and belief in conspiratorial forces is far from conclusive. Although individual religiosity is often positively, albeit moderately, associated with specific conspiracy beliefs and a general conspiracy mentality (e.g., Jasinskaja-Lahti and Jetten, 2019; Teličák and Halama, 2021;Yendell and Herbert, 2022;Frenken et al, 2023), some studies find no robust evidence for such an association (e.g., Čavojová et al, 2019;Lobato and Zimmerman, 2019;Farkhari et al, 2022;Ladini, 2022).…”
Section: Introductionmentioning
confidence: 99%